2008
DOI: 10.1016/j.evalprogplan.2008.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Homeless youths’ perceptions of services and transitions to stable housing

Abstract: Use of available services is low among homeless youths, and how youth make decisions to access services or seek housing is unclear. This study explored perspectives of current and former street youth about these processes. Recruited from the streets and a drop-in center, 27 youth ages 16-24, participated in individual qualitative interviews. Findings from consensual qualitative analyses indicated choices to use services were embedded within developing autonomy and identification with street lifestyles. Themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 18 publications
5
45
0
4
Order By: Relevance
“…26 Among our sample, each additional year of age was statistically associated with a greater likelihood of reporting difficulty in accessing services. In this study setting, youth services typically terminate between the ages of 21–24, compelling young adults to turn to adult services that may be problematic and present dangers.…”
Section: Discussion: Need For Youth-centric Easy To Access Servicesmentioning
confidence: 75%
“…26 Among our sample, each additional year of age was statistically associated with a greater likelihood of reporting difficulty in accessing services. In this study setting, youth services typically terminate between the ages of 21–24, compelling young adults to turn to adult services that may be problematic and present dangers.…”
Section: Discussion: Need For Youth-centric Easy To Access Servicesmentioning
confidence: 75%
“…Research undertaken with homeless people has already pointed out that the lives of the homeless do not revolve around accessing services, and that they often have other priorities which they may choose over using services (Garrett et al, 2008;Elissen et al, 2011). Additionally, the relationship between care avoiders and professionals seems to be heavily influenced by negative attitudes about professionals and service agencies (Behnia, 2008).…”
Section: Motivation and Choicementioning
confidence: 99%
“…One plausible explanation is that shared accommodation which may mirror a residential care environment, has been described as a 'hostel culture' exposing youth to negative peer attitudes/relationships (Ammerman et al, 2004) and is also associated with increased problematic behaviours among youth (Biehal et al, 1995). We found that although there were existing transitional living programmes, some youth may not utilise available assistance that could provide them a place to live for a successful transition (Garrett et al, 2008). This could further expose former foster youth to homelessness or situations where they often stay with peers experiencing difficult circumstance themselves and may exacerbate negative living situations (Ammerman et al, 2004).…”
Section: Discussionmentioning
confidence: 85%